Smartphone Donation for Education: A Technopreneurship’s Approach in Indonesian Case Study - Halim , Siana; A.Y. Aysia, Debora; Lestari, Jessi; Shu San, Gan (Universitas Ngeri Malang, 2023)
This paper proposed a smartphone donation to help Indonesian students in remote areas and students who needed help, such as students in orphanages in Indonesia, using the technopreneurship approach. The technopreneurship steps that we used in this study started with collecting data through a questionnaire to know the willingness of Indonesians to donate and their preferences in donating their used smartphones. We found that 78.7% of the respondents are eager to donate, and they trust the social, educational, and religious institutions as trusted, credible institutions as places for collecting used smartphones. However, online channels are more convenient for them to donate, followed by donations through religious institutions such as mosques, churches, viharas, and temples. As a result, a business model canvas and a business process are constructed to answer the eagerness of Indonesians to donate their used smartphones. Penelitian ini mengusulkan donasi smartphone untuk membantu pelajar Indonesia di daerah terpencil dan pelajar yang membutuhkan bantuan, seperti pelajar di panti asuhan di Indonesia, dengan menggunakan pendekatan technopreneurship. Langkah-langkah technopreneurship yang kami gunakan dalam penelitian ini dimulai dengan mengumpulkan data melalui kuesioner untuk mengetahui kesediaan masyarakat Indonesia untuk berdonasi dan preferensi mereka dalam mendonasikan smartphone bekas mereka. Kami menemukan bahwa 78,7% dari responden sangat ingin berdonasi, dan mereka mempercayai lembaga-lembaga sosial, pendidikan, dan keagamaan sebagai lembaga yang terpercaya dan kredibel sebagai tempat pengumpulan smartphone bekas. Namun, saluran online lebih nyaman bagi mereka untuk berdonasi, diikuti oleh donasi melalui lembaga keagamaan seperti masjid, gereja, vihara, dan kuil. Hasilnya, sebuah kanvas model bisnis dan proses bisnis dibangun untuk menjawab keinginan masyarakat Indonesia untuk mendonasikan smartphone bekas mereka.